Temtamy syndrome caused by a new C12orf57 variant in a Chinese boy, including pedigree analysis and literature review - Wang, Yanqin (Exp Ther Med, 2020)
Temtamy syndrome is an extremely rare disorder caused by chromosome 12 open reading frame 57 (C12orf57) pathogenic variants. The present study reported a boy with Temtamy syndrome displaying global developmental delay, epilepsy and dysmorphic facial appearance. Whole-exome sequencing was performed to identify a novel homozygous pathogenic variant of C12orf57 (c.3G >C, p.Met1IIe), and the affected protein structure and function were predicted to be pathogenic. Additionally, clinical features of the other reported 56 patients with C12orf57 pathogenic variants were reviewed and compared. This study highlighted that C12orf57 pathogenic variants are mainly associated with global developmental delay, epilepsy and dysmorphic facial appearances. The clinical features were in accordance with the previously reported cases, except for those with recurrent infection, but without corpus callosum abnormalities. The present study reported the first Asian case to the best of our knowledge with Temtamy syndrome, and the novel C12orf57 pathogenic variant has not reported in any ethnic groups previously. The present study expanded the spectrum of C12orf57 pathogenic variants as well as the ethnic backgrounds of the affected patients.